Tajalliyah Ash-Shira' fi Al-Adab Al-'Arabi Al-Mu'ashir wa Atsarihi fi Harb Al-'Arab - Halimi, Halimi; Faisol, M.; Al-Dakhiel, Muhammad Majed (UIN Maulana Malik Ibrahim Malang, 2018)
لقد عبر شعر الصراع (المقاومة والثورة والحرب) في بلاد الجزيرة العربية مفردات متنوعة طوال تاريخها من خلال البعدين، منهما البعد المكاني متمثلا في الأرض التي حملها الشعر دلالات ومعان تتجاوز ملامحها المادية لتكتسب بعدا روحيا وقيما عليا. والبعد الثاني يتمثل في البعد التراثي والتاريخي. فشعر الصراعات لا ينفصل من الواقع الاجتماعي، وليس هو الشعر الانعزالي، بل هو الشعر الاجتماعي الذي له علاقة متينة بواقعه، والذي يحمل رموزا تاريخية كثيرة نتيجة لامتداد العمر الزمني لهذا المجتمع من العصور القديمة، وكان المجتمع والأرض تصنع تقاليد تتطور إلى رموز، فهناك رمز للكرام وللمروءة ولمعاناة المجتمع وللصراع، وفي الرمز أسلوب فيه تلميح ومداره. Throughout the history of the Arab world, the poetry of the struggle (the resistance, the revolution and the war) has been a varied vocabulary throughout its history through the two dimensions, including the spatial dimension, in the land where poetry carries meanings and meanings that transcend its physical texture to acquire a spiritual dimension and supreme value. It is the social poetry that has a strong relationship to its reality, which carries many historical symbols as a result of the extension of the temporal age of this society from antiquity. The society and the land made traditions that evolve into symbols. And the suffering of society and the conflict and the virus, and in the code style in which the tip and orbit.